Rancang Bangun Sistem Financial Accounting Standars Berbasis Website Pada CV. Hartop Jaya - Riris Lima Putri; Dede Handayani (SAINSTECH: JURNAL PENELITIAN DAN PENGKAJIAN SAINS DAN TEKNOLOGI, 2023)
Abstract The financial accounting standard system is the system used to manage financial data at CV Hatop Jaya. In today's digital era, the use of web technology and scrum methods can be used to develop a more efficient and accurate financial accounting standard system. This study aims to design and develop a web-based financial accounting standard system using the Scrum method. The Scrum method is used throughout the system development process, from requirements analysis to testing. By using the Scrum method, this research enables the development of a more structured and adaptive web-based financial accounting standard system. Researchers can leverage the principles of Scrum to ensure needs are met efficiently and set the right priorities. This research is expected to contribute to the development of a more efficient financial accounting standard system. The Scrum method still provides a framework that is focused, organized, and responsive to change, thereby helping researchers manage financial data and create financial reports more effectively within the scope of work performed. The system developed in this study can be used by CV Hartop Jaya to manage their financial data and make financial reports easily and quickly. In addition, this research can also be a reference for further research in developing a web-based financial accounting standards system.programming language and uses the MySql Database because it is more accessible to users. Keywords: financial, accounting, Scrum